Different risk factor patterns for adult asthma, rhinitis and eczema: results from West Sweden Asthma Study. Issue 1 (4th August 2016) - Rönmark, Erik P.; Ekerljung, Linda; Mincheva, Roxana; Sjölander, Sigrid; Hagstad, Stig; Wennergren, Göran; Rönmark, Eva; Lötvall, Jan; Lundbäck, Bo
Abstract: Background: Atopic diseases including asthma, rhinitis and eczema have increased in the second half of the past century. This has been well studied among children and adolescents but with the exception of asthma to a much lesser extent in adults. The adult risk factor pattern of atopic diseases, in particular of eczema, and their relation to allergic sensitization are yet to be fully elucidated. Studies among adults that have compared the risk factor pattern for these conditions in the same material are very few. The objective of this study was to compare the risk factor patterns for asthma, rhinitis and eczema in a randomly selected adult population. Methods: A questionnaire survey on atopic diseases was dispatched by mail to 30, 000 randomly selected individuals in West Sweden aged 16–75 years and 62 % participated. A subgroup of 2000 individuals was selected for clinical examinations including blood sampling for specific serum Immunoglobulin E to common airborne allergens and 1172 attended. Results: The prevalence of current asthma was 11.8 %, current rhinitis 42.8 %, current eczema 13.5 and 2.3 % had all three conditions while 13.9 % had at least two conditions. No mutual risk factor was identified for all three conditions. Allergic sensitization was a strong risk factor for current asthma (OR 4.1 CI 2.7–6.3) and current rhinitis (OR 5.1 CI 3.8–6.9) but not so for current eczema. Obesity was a risk factor for current asthma and current rhinitis, while farm childhood decreased the risk for current asthma and current rhinitis. Occupational exposure to gas dust or fumes and female sex was associated with an increased risk of current asthma and current eczema. Conclusions: There are different risk factor patterns for asthma, rhinitis and eczema in adults but some risk factors are overlapping between some of the conditions. The effect of mutable risk factors should be assessed further in longitudinal studies.